2020
DOI: 10.1080/1331677x.2019.1708769
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty and dividend sustainability: new insight from emerging equity market of China

Abstract: We examine the influence of Economic Policy Uncertainty (E.P.U.) on dividend sustainabilitydividend termination and dividend initiation decision. Using a sample of 1,375 firms over the time span 2000-2015, our main result reveals that during high E.P.U. past dividend payers are more likely to terminate and past nonpayers are less likely to initiate dividends. However, firms that rely more on internal finance (I.F.), generate high return on invested capital (R.O.I.C.) and state-owned enterprises (S.O.E.s) are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The author used TA as a proxy for liquidity and discovered that it was statistically significant at the 1% level in both estimations, with the higher coefficient value of 0.0194 in sys‐GMM implying that the liquidity factor was more pervasive and significant in the Chinese market (An et al., 2020). Finally, the dividend yield is significantly and positively associated at a 1% level with the higher coefficient value of 1.452 in sys‐GMM, consistent with the findings (Cheung et al., 2015; Sarwar et al., 2020). This implies that firms listed on the SZSE are more likely to pay dividends because they have a higher profit margin, a large cash position, are low leveraged, and are considering a subsequent equity offering.…”
Section: Resultssupporting
confidence: 88%
“…The author used TA as a proxy for liquidity and discovered that it was statistically significant at the 1% level in both estimations, with the higher coefficient value of 0.0194 in sys‐GMM implying that the liquidity factor was more pervasive and significant in the Chinese market (An et al., 2020). Finally, the dividend yield is significantly and positively associated at a 1% level with the higher coefficient value of 1.452 in sys‐GMM, consistent with the findings (Cheung et al., 2015; Sarwar et al., 2020). This implies that firms listed on the SZSE are more likely to pay dividends because they have a higher profit margin, a large cash position, are low leveraged, and are considering a subsequent equity offering.…”
Section: Resultssupporting
confidence: 88%
“…Current study uses a more balanced set of data. Current research was an extension of study conducted by Sarwar et al (2020) to explore the difference in the presence of a more financially expert board and their way of looking into the dividend matters at the time of EPU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, study pertains to managerial implications regarding devising board financial expertise policies for betterment of market. As argued by Sarwar et al, (2020) for improving corporate governance of a firm, it is critical to have at least one financial expert on board who can better off with market synchronized decision-making to benefit the firm. That paper also argued, even at the time of economic policy uncertainty, a financial expert can exactly shape a decision to remain efficient in earning as well as to sustain market position in front of existing as well as prospective investors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it will be a challenge to find alternatives energy sources that will not harm the economic performance of the country. Ikhidi, (2015) and Sarwar, Ming & Husnain (2020) attempted to find a connection non-RE, RE and GDP in Nigeria. They studied quarterly data of 1971-2013 and found that RE is contributing more towards GDP as compared to non-RE.…”
Section: Renewable Energy Gdp and Co2 Emissionsmentioning
confidence: 99%